Rationale and Design for a Monocentric Prospective Study: Sleep Apnea Diagnosis Using a Novel Pacemaker Algorithm and Link With Aldosterone Plasma Level in Patients Presenting With Diastolic Dysfunction (SAPAAD Study). Issue 12 (6th January 2018) - Champ-Rigot, Laure; Ferchaud, Virginie; Prévost, Jean-Noël; Moirot, Pierre; Pellissier, Arnaud; Legallois, Damien; Alexandre, Joachim; Scanu, Patrice; Morello, Remy; Saloux, Eric; Milliez, Paul Ursmar
Previous studies showed good agreement between pacemaker respiratory disturbance index (RDI) and polysomnography for diagnosis of severe sleep apnea (SA). The aim of this study is to investigate the diagnostic accuracy of RDI compared with apnea-hypopnea index (AHI) from a cardiorespiratory sleep study for the diagnosis of severe SA within patients requiring a pacemaker and meeting diastolic dysfunction criteria. Secondary objectives are as follows: correlation between plasma aldosterone level and SA severity, diagnostic accuracy of RDI for moderate SA, prevalence of SA among patients with diastolic dysfunction, occurrence of arrhythmias, and improvement of RDI with continuous positive airway pressure therapy. We designed a monocentric prospective nonrandomized study of prevalent cases to include 68 patients with a 6-month follow-up. Both RDI and AHI will be compared 2 months after implantation and after 1 month of continuous positive airway pressure treatment in patients with severe SA. This is the first study that examines diagnostic accuracy of pacemaker algorithm for the diagnosis of SA and correlation with plasma aldosterone levels in patients with diastolic dysfunction. Protocol version: V04. 04/04/2017 Trial registration: ClinicalTrials.gov NCT02751021